2002
DOI: 10.1016/s1010-7940(01)01095-8
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of injury in blunt traumatic rupture of the aorta

Abstract: Rupture of the aorta accounts for a significant proportion of fatalities following blunt trauma. A great deal of consensus exists describing the circumstances under which acute traumatic aortic dissection occurs as well as its investigation and management. However, there remains some controversy surrounding the pathogenic aetiology underlying this injury. Univariate and multivariate models of blunt traumatic aortic rupture (BTAR) are discussed. To account for the consistency in the nature of BTAR, despite a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
119
0
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(133 citation statements)
references
References 26 publications
0
119
0
14
Order By: Relevance
“…Former studies showed that the aortic rupture was detected in 10-15% of vehicle mortalities and that it was the primary cause of death in a high percentage of cases [1,29,33,34]. Richens et al [2] mentioned an occurrence of blunt traumatic aortic ruptures in 20% of all automobile fatalities and a scene survival of the victim of 2-5%. Following Pongratz et al [3] a rupture of the descending thoracic aorta is the second most common cause of death after the most common cause, the traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former studies showed that the aortic rupture was detected in 10-15% of vehicle mortalities and that it was the primary cause of death in a high percentage of cases [1,29,33,34]. Richens et al [2] mentioned an occurrence of blunt traumatic aortic ruptures in 20% of all automobile fatalities and a scene survival of the victim of 2-5%. Following Pongratz et al [3] a rupture of the descending thoracic aorta is the second most common cause of death after the most common cause, the traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, most of the casualties with aortic ruptures were found in not belted situations. The former studies [2,10] pointed out a rapid chest deceleration as an important factor for the occurrence of aortic ruptures whereas in newer studies [15,16,35] the chest deceleration is mostly mentioned as a side effect along with chest compression and should not be the main influencing factor for such kind of severe injury.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic rupture occurs at this site in 80% of pathological series and in 90% of the clinical series Thompson & Morgan., 2009). Despite advances in surgical techniques, in emergency settings, open surgical repair of aortic rupture is still associated with a mortality rate of 18%-67% (Steingruber et al, 2007, Karmy-Jones et al 2003Richens et al, 2002;Williams et al, 1994). Most series report the technical success of TEVAR to be 81.1-100%, with a paraplegia rate of 0%.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic aortic injuries are associated with high mortality and are the second most common cause of death in trauma patients after intracranial hemorrhage (1). Thoracic aortic dissection is usually a result of sudden deceleration caused by a traffic accident or fall.…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic aortic dissection is usually a result of sudden deceleration caused by a traffic accident or fall. The most common rupture location is the aortic isthmus (i.e., the region between the fixed aortic arch and mobile thoracic aorta) (1,2).…”
Section: Introductionmentioning
confidence: 99%